Applying the Kaizen in Africa 2018
DOI: 10.1007/978-3-319-91400-8_4
|View full text |Cite
|
Sign up to set email alerts
|

Kaizen and Standardization

Abstract: There are many methods and concepts of Kaizen that can be used to achieve quality and productivity improvements. Most of these originated in the West in line with the desire to improve production management. These were imported to Japan, improved and modified to suit the industrial climate and corporate culture of that country. Together with those aspects independently developed in Japan, they were further developed as Kaizen. As this was the driving force for high economic growth in post-war Japan, it became … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…However, it was commented widely that there was a lack of consultation in the development of the standard with global lean six sigma and OPEX practitioners, key academics and two leading professional quality bodies, in particular the Japanese Union of Scientists and Engineers (JUSE) and the American Society for Quality (ASQ) (Roser, 2016;Morgan, 2017). Kazakova (2021), Kikuchi and Suzuki (2018), Ishiyama (2016) and all concluded that the publication of the standard would not impact industries, as it would be too expensive and problematic for small and medium sized enterprises (SMEs) to implement and that the introduction of a standard was premature. The low uptake of the standard supports these themes in terms of certification.…”
Section: Critical Reception Of Iso 18404mentioning
confidence: 99%
See 2 more Smart Citations
“…However, it was commented widely that there was a lack of consultation in the development of the standard with global lean six sigma and OPEX practitioners, key academics and two leading professional quality bodies, in particular the Japanese Union of Scientists and Engineers (JUSE) and the American Society for Quality (ASQ) (Roser, 2016;Morgan, 2017). Kazakova (2021), Kikuchi and Suzuki (2018), Ishiyama (2016) and all concluded that the publication of the standard would not impact industries, as it would be too expensive and problematic for small and medium sized enterprises (SMEs) to implement and that the introduction of a standard was premature. The low uptake of the standard supports these themes in terms of certification.…”
Section: Critical Reception Of Iso 18404mentioning
confidence: 99%
“…Kazakova (2021), Kikuchi and Suzuki (2018), Ishiyama (2016) and all concluded that the publication of the standard would not impact industries, as it would be too expensive and problematic for small and medium sized enterprises (SMEs) to implement and that the introduction of a standard was premature. The low uptake of the standard supports these themes in terms of certification.…”
Section: Critical Reception Of Iso 18404mentioning
confidence: 99%
See 1 more Smart Citation
“…There is a lack of consultation and involvement of LSS practitioners, government bodies and professionals in developing the standard (Morgan, 2017). However, several authors (Kikuchi and Suzuki, 2018;Kazakova, 2021) commented that the publication of any standard does not mean it would work effectively for the purpose it was developed. Similarly, the study performed by Antony et al (2021a) stated that the organization has low uptake of ISO 18404 standard adoption.…”
Section: Introductory Reception Of Iso 18404:2015mentioning
confidence: 99%